2015
DOI: 10.1007/s10286-015-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic reactivation in children: influence of two various modes of exercise

Abstract: These results suggest that parasympathetic reactivation is likely greater following exercises that use smaller muscle mass (arm cranking) rather than larger muscle mass (cycling) in healthy boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…During the 5 min recovery period, it was reported that HR recovery as well as the recovery of RMSSD was more rapid following exercise involving a smaller muscle mass or energy expenditure (i.e., cycling > walking > running), with the authors therefore concluding that muscle mass and/or energy expenditure are determinants of post-exercise parasympathetic reactivation. Similarly, active children demonstrated more rapid HR and HRV recovery following maximal incremental arm-cranking vs. cycling (Ahmadian et al, 2015), The findings of these two studies were also consistent with those of other studies investigating HR recovery (without HRV measurement) following exercise mode comparisons such as cycling vs. running (Rahimi et al, 2006; Maeder et al, 2009) and cycling vs. arm-cranking (Ranadive et al, 2011). These studies also utilized maximal incremental exercise.…”
Section: Hrv During Post-exercise Recoverysupporting
confidence: 80%
See 1 more Smart Citation
“…During the 5 min recovery period, it was reported that HR recovery as well as the recovery of RMSSD was more rapid following exercise involving a smaller muscle mass or energy expenditure (i.e., cycling > walking > running), with the authors therefore concluding that muscle mass and/or energy expenditure are determinants of post-exercise parasympathetic reactivation. Similarly, active children demonstrated more rapid HR and HRV recovery following maximal incremental arm-cranking vs. cycling (Ahmadian et al, 2015), The findings of these two studies were also consistent with those of other studies investigating HR recovery (without HRV measurement) following exercise mode comparisons such as cycling vs. running (Rahimi et al, 2006; Maeder et al, 2009) and cycling vs. arm-cranking (Ranadive et al, 2011). These studies also utilized maximal incremental exercise.…”
Section: Hrv During Post-exercise Recoverysupporting
confidence: 80%
“…HRV has also been employed as a tool to investigate post-exercise autonomic (predominantly parasympathetic) activity (Goldberger et al, 2006; Buchheit et al, 2007a, 2009a; Al Haddad et al, 2010; Stanley et al, 2013; Ahmadian et al, 2015). Upon exercise cessation, HR and HRV demonstrate a time-dependent recovery and eventual return to pre-exercise levels (Stanley et al, 2013).…”
Section: Hrv During Post-exercise Recoverymentioning
confidence: 99%
“…These results can be supported by the physiological responses of the cardiovascular system to sedentary behaviour. Subjects with reduced mobility in the lower limbs activate physiological mechanisms of cardiac autonomic control, increasing HR in order to restore pressure and blood volume [27,28]. There are limited data available to support this responses in SB subjects [14].…”
Section: Discussionmentioning
confidence: 99%
“…Data and statistical analysis HRR was calculated by the difference between the maximal HR and HR obtained punctually at the first and second minutes at recovery phase during the active cool-down period [HRR_1 = HR peak -HR at the first minute of recovery and HRR_2 = HR peak -HR at the second minute of recovery] [27]. The heart rate peak was the maximal heart rate obtained in the final test and peak oxygen uptake was calculated as the mean value over the final 30 seconds of the test.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, HRV and HRR have been examined following moderate or maximal exercise (Ahmadian, Roshan, & Hosseinzadeh, 2015;Goulopoulou, Fernhall, & Kanaley, 2009;Goulopoulou et al, 2006;Medeiros, del Rosso, Leicht, Hautala, & Boullosa, 2017;Perkins, Jelinek, Al-Aubaidy, & de Jong, 2017). However, a few studies have investigated HRV and HRR following high intensity exercise (e.g., Wingate test) with the recovery of the vagal and sympathetic nervous systems dependent upon the exercise intensity undertaken (Pierpont & Voth, 2004).…”
Section: Introductionmentioning
confidence: 99%